Purificación de la papaína del látex de la lechosa y cuantificación de la actividad enzimática (Agroindustria, Sociedad y Ambiente, 2018)
Latex is a thixotropic fluid contained in latiferous vessels under the exocarp of the papaya. Its content of proteolytic enzymes has made it a highly studied subject, in particular papain, which, even being among the minor constituents of these enzymes, it has the highest industrial use. In this investigation papain was purified from papaya latex and the effect of two drying conditions on enzyme activity was evaluated. The latex was extracted from the fruit´s exocarp, dehydrated under two conditions (C), C1: 25ºC and 20 h and C2: 60ºC and 4 h, the dry yield was calculated and characterized. Subsequently, the papain was purified and quantified the enzymatic activity; then the purification factor (FP) was estimated and finally, the proteolytic activity was determined by evaluating the efficiency of removal of proteins from an industrial effluent. The dry latex in C1, with a yield of 1.38%, was characterized by having 52 ° Brix, pH 6.26, humidity 8.50%, 39.48% ash; while in C2 yield 1.45%, 42.96 ° Brix, pH 6.76, humidity 4.73%, 30.80% ash. The FP was 91.19-108.64%. Finally, the power of the enzyme was demonstrated by determining the efficiency of removal of the protein content of a dairy effluent. With the purified papain, an average protein removal of 60.03% was achieved
Keywords: Carica papaya L.; alcohol extraction in two steps; Balls and Hoover; dairy effluent